2014
DOI: 10.1161/circgenetics.114.000703
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Mutation of the SCN5A Gene Causes Exercise-Induced Polymorphic Ventricular Arrhythmias

Abstract: Background-Over the past 15 years, a myriad of mutations in genes encoding cardiac ion channels and ion channel interacting proteins have been linked to a long list of inherited atrial and ventricular arrhythmias. The purpose of this study was to identify the genetic and functional determinants underlying exercise-induced polymorphic ventricular arrhythmia present in a large multigenerational family. Methods and Results-A large 4-generation family presenting with exercise-induced polymorphic ventricular arrhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 40 publications
1
61
0
Order By: Relevance
“…In cardiac cells, mutations in more than 30 genes encoding ion channels have been associated with an increasingly wide range of inherited cardiac arrhythmias [1]. Examples of genetic cardiac disorders include congenital ectopic Purkinje-related premature contractions (MEPPC) and exercise induced polymorphic ventricular tachycardia (EPVT) which have been linked to the presence of the Na v1.5 -p.R222Q and Na v1.5 -p.I141V mutations [24]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac cells, mutations in more than 30 genes encoding ion channels have been associated with an increasingly wide range of inherited cardiac arrhythmias [1]. Examples of genetic cardiac disorders include congenital ectopic Purkinje-related premature contractions (MEPPC) and exercise induced polymorphic ventricular tachycardia (EPVT) which have been linked to the presence of the Na v1.5 -p.R222Q and Na v1.5 -p.I141V mutations [24]. …”
Section: Introductionmentioning
confidence: 99%
“…The observed arrhythmia disappears under exercise [2, 3]. For Na v1.5 -p.I141V carriers, the ECG is characterized by an increased sinus rate, atrial tachyarrhythmias, and an increased number of ventricular complexes during exercise [4]. On the molecular level, these mutations affect the biophysical properties of Na v1.5 by shifting its voltage dependence of steady state of activation towards more negative potentials and accelerating its activation and inactivation kinetics [26].…”
Section: Introductionmentioning
confidence: 99%
“…1A-F). 3,4 For both channels, the presence of the p.I141V mutation shifted the voltage dependence of activation toward negative potentials (Na v 1.4-V 1/2 act : ¡18 § 1.4 mV, n D 9, versus ¡28 § 2.1 mV, n D 5, ***P < 0.001; slope: 5.3 § (E and F) Steady-state activation and inactivation curves for Na v 1.4 (E) and Na v 1.5 (F). Activation properties were determined from I/V relationships by normalizing peak I Na to driving force and maximal I Na .…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] This study investigated the biophysical effects of the p.I141V mutant on these channels and demonstrated that the p.I141V substitution stabilized the activated state of the DI VSD, manifested by a negative shift of the voltage dependence of the activation curve.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation